Analisis Gaya Bahasa Dalam Lirik Lagu “Alexandra” Karya Hindia - Ridho Rahmatulloh; Arfian Suryasuciramadhan; Muhamad Sobahri; Muhamad Fauzan Kurniawan; Aldo Savero Zahran (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Literature is a type of artwork that blends the beauty of language with the intent to convey an idea or message. Literature is very important for human life because it can influence human thinking and perspective. Song lyrics are one type of literary work that can move feelings in a beautiful and interesting way. One of the poets / songwriters of the country is the Indies. He is a solo singer with the real name "Baskara Putra". Her song titled "Alexandra" is one of the songs that made her famous in the country. The words used in the lyrics contain many styles of language or figurative words. Therefore, the author intends to analyze the style of language used in the lyrics of Alexandra's song to add insight to the audience